Radec Model : Improving Elementary Students’ Environmental Care And Science Literacy Through Energy Source Materials - Herawati, Netty; Novita, Lina; Jaenudin, Dadang (Universitas Pakuan, 2024)
This study investigates the impact of the RADEC (Read, Answer, Discuss, Explain, and Create) learning model on scientific literacy skills and environmental care character among 4th-grade elementary students in Indonesia. Using a quasi-experimental design with pretest-posttest control group, the research focused on energy source materials. The experimental group received RADEC instruction, while the control group used Problem-Based Learning. Results showed significant improvements in scientific literacy across all indicators (explaining phenomena scientifically, evaluating and designing scientific investigations, and interpreting data and scientific evidence) for the RADEC group. Similarly, students' environmental care character enhanced in various aspects, including school and classroom environment management, waste and energy management, and planning clean environment programs. The RADEC model's structured approach, emphasizing independent exploration and critical thinking, proved more effective than traditional methods in fostering scientific literacy and environmental awareness. The study concludes that RADEC offers a promising framework for enhancing science education and environmental consciousness in elementary schools, with implications for curriculum development and teaching practices in the context of 21st-century skills and digital literacy.